Eating Disorders: A Personal Story With Implications for Dentists, Educators and Healthcare Professionals - Meredith Ypma; Kenneth R. Etzel; Michael A. Siegel (MedEdPORTAL, 2011)
Abstract This resource is a stand-alone video presentation that can be used in the classroom, small-group sessions, or continuing education courses, or by individuals as an interprofessional means of attaining a better understanding of the psychosocial, physiologic, emotional, and dental clinical management aspects of eating disorders. The video chronicles the experience of a dental student who overcame an eating disorder. The featured speaker (author MY) describes how her eating disorder first “came out” following a biochemistry lecture during her dental education. The faculty member involved (author KRE) was instrumental in helping her cope with the rigors of dental school and was intimately involved in her recovery. This presentation was based on a symposium put on by the authors at a national dental meeting. The audience response was so overwhelming that it was decided to share this story worldwide. The video is approximately 1 hour long. This length makes it an ideal substitute for a classroom lecture. If utilized in a small-group learning environment, the video can be followed by facilitator-led discussion; for such a use, a time period of 90 minutes to 2 hours would be needed. This presentation is the true life story of one of the authors. Its effectiveness is evident in the emotion it creates in the audience.